Antibiotics exposure and risk of inflammatory bowel disease: a systematic review. (2nd January 2018) - Theochari, Nikoletta A.; Stefanopoulos, Anastasios; Mylonas, Konstantinos S.; Economopoulos, Konstantinos P.
Abstract: Aim: The aim of this study was to critically assess all available evidence suggesting an association between antibiotic exposure and new onset of inflammatory bowel disease (IBD). Materials and methods: This systematic review was conducted according to the PRISMA statement and eligible studies were identified through search of PubMed, Embase and the Cochrane Library. Data on patient demographics, antibiotic exposure and confounding factors were analyzed. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of eligible studies. Results: A total of 15 observational studies (10 case control and five cohort) including 8748 patients diagnosed with IBD were systematically reviewed. Antibiotic exposure was mostly associated with Crohn's disease but not with ulcerative colitis. In particular, penicillin's, cephalosporins, metronidazole and fluoroquinolones were most commonly associated with the onset of Crohn's disease. The impact of tetracycline-family antibiotics on the pathogenesis of IBD was not clear. Conclusion: There may be an association between antibiotic exposure and the development of IBD; especially Crohn's disease. Even though, clinicians should be cautious when prescribing certain antibiotic regimens to patients with a strong family history of IBD, it should be emphasized that available data are not granular enough to reach any definitive conclusions.